2022
DOI: 10.1007/s12008-022-00839-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additive manufacturing processes on part defects and properties: a classification review

Abstract: Additive manufacturing (AM) is an established manufacturing technology which allows for greater design freedom. Across the seven existing AM processes, we observe a variety of defects in printed parts, due to the different physical properties of each manufacturing process. This variety of defects complicates the design step without a clear overview of the deep interaction geometry-process-defect. The classification of these defects, which may be process-or machine-based, often raises methodological and termino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 141 publications
0
6
0
Order By: Relevance
“…This information enables them to refine their printing parameters, adjust material formulations, optimize post-processing techniques, and implement corrective actions to reduce the occurrence of defects in future prints. Defects like cracks, delamination, and dimensional inaccuracies can impact mechanical properties and surface finish [23]. Identifying these defects post-processing allows corrective measures such as heat treatment or surface finishing to meet quality standards.…”
Section: Post-process Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…This information enables them to refine their printing parameters, adjust material formulations, optimize post-processing techniques, and implement corrective actions to reduce the occurrence of defects in future prints. Defects like cracks, delamination, and dimensional inaccuracies can impact mechanical properties and surface finish [23]. Identifying these defects post-processing allows corrective measures such as heat treatment or surface finishing to meet quality standards.…”
Section: Post-process Defectsmentioning
confidence: 99%
“…Quality control is paramount in BJ-AM to produce high-quality components with precise dimensional accuracy and mechanical integrity [20,21]. According to statistical data, defects such as warping, deformation, rough surfaces, and low dimensional accuracy are prevalent in BJ printing processes, leading to suboptimal part performance [22][23][24]. For instance, studies have shown that porosity levels ranging from ~2.7% [25] to ~16.4% in BJ-printed components can significantly impact mechanical strength, thermal conductivity, and electrical conductivity [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This contraction can vary unpredictably due to factors such as the thermal coefficient of the material, print orientation, layer height, and cooling rates, leading to dimensional inaccuracies in the final product (Fitzharris et al, 2018). The repercussions of shrinkage are multifaceted, influencing not only the geometric fidelity but also the mechanical performance and assembly compatibility of the parts (de Pastre et al, 2022). For industries where precision is not just a quality marker but a critical requirement (e.g., aerospace, biomedical implants, and precision engineering) the repercussions of shrinkage are not merely a limit but a barrier to application (Srivastava and Rathee, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Among production processes, additive manufacturing solutions offer several advantages, particularly fast production from a CAD design file [ 1 , 2 ] to the final product and the possibility of producing near-net-shape complex geometries without additional operations while avoiding material waste [ 2 ]. Additive manufacturing includes different technologies and diversifies from polymer, ceramics, and metallic materials [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%